2012
DOI: 10.1111/j.1440-1843.2012.02201.x
|View full text |Cite
|
Sign up to set email alerts
|

Tobacco smoke exposure and allergic sensitization in children: A propensity score analysis

Abstract: Background and objective There is conflicting evidence of the effect of environmental tobacco smoke (ETS) on the development of allergic diseases in children. Studies have shown that this relationship differs depending on maternal history of the disease. We sought to employ the rigor of propensity score methods to assess this relationship using data from a birth cohort. Methods Using n=662 children from the Wayne County Health, Environment, Allergy and Asthma Longitudinal Study (WHEALS) we assessed the relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
26
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 24 publications
(40 reference statements)
2
26
0
Order By: Relevance
“…Our results are consistent with earlier observations from several large prospective cohorts and cross-sectional studies demonstrating higher risks of atopic asthma, eczema and rhinitis in children exposed to ETS,1 6 19 33 42 46 as well as with the latest reports confirming its detrimental effect on the incidence of asthma in children. 2 40 42 47 However, in this report we included only studies assessing the influence of ETS exposure on objective markers of allergic sensitisation, and not the studies assessing particular allergic disease (asthma, atopic eczema, hay fever, wheezing) as an outcome.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our results are consistent with earlier observations from several large prospective cohorts and cross-sectional studies demonstrating higher risks of atopic asthma, eczema and rhinitis in children exposed to ETS,1 6 19 33 42 46 as well as with the latest reports confirming its detrimental effect on the incidence of asthma in children. 2 40 42 47 However, in this report we included only studies assessing the influence of ETS exposure on objective markers of allergic sensitisation, and not the studies assessing particular allergic disease (asthma, atopic eczema, hay fever, wheezing) as an outcome.…”
Section: Discussionsupporting
confidence: 93%
“…The four studies eligible for meta-analysis involved 6629 participants (2161 ETS-exposed and 4468 non-exposed) with moderate heterogeneity calculated at I 2 =54% (p=0.09) 5 6 21 33. The FE estimate demonstrated that ETS exposure increased the risk of allergic sensitisation (OR=1.12; 95% CI 1.00 to 1.25), and the effect was on the border of statistical significance (p=0.06).…”
Section: Environmental Tobacco Smoke and Specific Igementioning
confidence: 99%
See 1 more Smart Citation
“…43 The inverse association may either reflect selective avoidance of smoking or immuno-suppressive effects of tobacco smoke. 42, 44 Some studies report that those with asthma and allergies in childhood are less likely to initiate smoking than their healthy peers.…”
Section: Discussionmentioning
confidence: 99%
“…The rationale behind the study is the knowledge that tobacco smoking is an established risk factor for a large number of major diseases including cancer, but seemed to be protective against allergic sensitization, when allergy is not yet established1415161718. The inverse correlation of smoking to allergic sensitization and cancer risk is striking and suggests that smoking may be causative in the aberrant immune regulation of both diseases.…”
mentioning
confidence: 99%